Simulation of helicopter noise in maneuvering flight - Gennaretti, M.; Serfini, J.; Molica Colella, M.; Bernardini, G. (My University, 2014)
This paper deals with methodologies for evaluation of acoustic disturbance emitted by helicopter main rotors in unsteady maneuvers. The attention is focused on those techniques applied in minimumnoise, optimal trajectories search tools. Typically, noise optimization processes are based on noise estimations conceived as sequences of steady-state flight acoustic predictions, properly selected from dedicated databases. Introducing a multidisciplinary rotor solution procedure including accurate aerodynamic, aeroelastic and aeroacoustic prediction tools suited for unsteady maneuver analyses, this work presents an assessment of methods used for acoustic disturbance identification based on different characterization parameters for correlating unsteady flight conditions with steady-state flight radiated noise. Only the main rotor component is examined, although tail rotor contribution might be included, as well. The numerical investigation concerns a lightweight helicopter model in unsteady flight, and provides comparisons between noise predicted by the considered methods in terms of sound pressure levels on a hub-centered hemisphere rigidly connected to helicopter.